2012
DOI: 10.1017/s0950268812001598
|View full text |Cite
|
Sign up to set email alerts
|

Group B streptococcal colonization and the risk of pre-eclampsia

Abstract: SUMMARYTo determine if there was an association between recto-vaginal group B streptococcus (GBS) colonization and pre-eclampsia, two cross-sectional studies were conducted using statewide hospital databases. The first study analysed data from the state of Florida, USA, and included 190 645 women who were discharged in 2001. This dataset was used to generate the hypothesis that GBS colonization is associated with pre-eclampsia. The second study tested the GBS hypothesis using t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
8
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 34 publications
(35 reference statements)
3
8
1
Order By: Relevance
“…The study reached the same conclusion found in the early 2000’s report using statewide hospital databases in Florida and Texas [26]. Interestingly, our study population had a much greater reduction (59%) than was found for the Florida (27%) and Texas (30%) cohorts.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…The study reached the same conclusion found in the early 2000’s report using statewide hospital databases in Florida and Texas [26]. Interestingly, our study population had a much greater reduction (59%) than was found for the Florida (27%) and Texas (30%) cohorts.…”
Section: Discussionsupporting
confidence: 90%
“…There was no correlation between GBS colonization and incidence of preeclampsia. The overall GBS colonization and preeclampsia rates were much higher than those found in the present study and in the Florida/Texas cohorts study [26]. It is not clear if the 35% black patients, or the other race/ethnic groups present (44% white, 21% unknown) contributed to such high GBS colonization and preeclampsia rates.…”
Section: Discussioncontrasting
confidence: 89%
See 2 more Smart Citations
“…The experimental result indicated a decreased number of Streptococcus species in the PE group, thus suggesting that Streptococcus bacteria may be correlated with the occurrence of PE (Chang et al 2020 ). Other research (Mulla et al 2013 ) has suggested that Streptococcus may be associated with tumor necrosis factor (TNF)-alpha, interleukin-6 (IL-6), and other cytokines. Streptococcus induced TNF-α (Zaga et al 2004 ; Kwak et al 2000 ; Rosati et al 1998 ; Hunolstein et al 1997 ) and IL-6 (Zaga et al 2004 ; Kwak et al 2000 ; Rosati et al 1998 ).…”
Section: Discussionmentioning
confidence: 99%